2013
DOI: 10.1007/s10456-013-9389-y
|View full text |Cite
|
Sign up to set email alerts
|

A peptide derived from TIMP-3 inhibits multiple angiogenic growth factor receptors and tumour growth and inflammatory arthritis in mice

Abstract: The binding of vascular endothelial growth factor (VEGF) to VEGF receptor-2 (VEGFR-2) on the surface of vascular endothelial cells stimulates many steps in the angiogenic pathway. Inhibition of this interaction is proving of value in moderating the neovascularization accompanying age-related macular degeneration and in the treatment of cancer. Tissue inhibitor of metalloproteinases-3 (TIMP-3) has been shown to be a natural VEGFR-2 specific antagonist—an activity that is independent of its ability to inhibit me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 44 publications
(51 reference statements)
0
30
0
Order By: Relevance
“…An investigation conducted by Kerr and Olson (1970) observed the formation of granulomatous pannus in the medullary spaces of chickens inoculated experimentally or contact-infected with MS. The present study demonstrated that several proangiogenic factors were upregulated, including ECM1 (Mongiat et al, 2003), IL-8 (Bodolay et al, 2002), TGF-β2 (Elshabrawy et al, 2015), SAA (Connolly et al, 2016), MMP-9 (Burrage et al, 2006), NRP1 (Kong et al, 2010), GLUL (Eelen et al, 2018), and THBS2 (Park et al, 2004), while antiangiogenic factors, including RGCC (An et al, 2009), as well as TIMP3 (Chen et al, 2014), were downregulated at both the mRNA and protein levels. These findings suggest that MS-infected CSF may contribute to blood vessel growth, which is necessary for sustaining pannus formation and the arthritis process.…”
Section: Il-8mentioning
confidence: 53%
See 1 more Smart Citation
“…An investigation conducted by Kerr and Olson (1970) observed the formation of granulomatous pannus in the medullary spaces of chickens inoculated experimentally or contact-infected with MS. The present study demonstrated that several proangiogenic factors were upregulated, including ECM1 (Mongiat et al, 2003), IL-8 (Bodolay et al, 2002), TGF-β2 (Elshabrawy et al, 2015), SAA (Connolly et al, 2016), MMP-9 (Burrage et al, 2006), NRP1 (Kong et al, 2010), GLUL (Eelen et al, 2018), and THBS2 (Park et al, 2004), while antiangiogenic factors, including RGCC (An et al, 2009), as well as TIMP3 (Chen et al, 2014), were downregulated at both the mRNA and protein levels. These findings suggest that MS-infected CSF may contribute to blood vessel growth, which is necessary for sustaining pannus formation and the arthritis process.…”
Section: Il-8mentioning
confidence: 53%
“…The growth of new blood vessels requires the breakdown of the surrounding ECM. Principal enzymes involved in this process include MMPs (Chen et al, 2014), as well as a family of zinc-containing, calcium-dependent proteinases that degrade major components of ECM (Murphy et al, 2002). Although collagenases (i.e., MMP-1, -8, and -13), gelatinases A and B (i.e., MMP-2 and -9), stromelysins (i.e., MMP-3, -10, and -11), and matrilysins (i.e., MMP-7 and -26) are expressed at low levels in normal human joint tissues, they are highly expressed in arthritic joints (Elshabrawy et al, 2015).…”
Section: Il-8mentioning
confidence: 99%
“…; Chen et al. ; Qi & Anand‐Apte ). Tissue inhibitors of metalloproteinase‐3 overexpression reduced tumour growth, angiogenesis and inflammation (Ahonen et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Chen et al. ; Das et al. ) and TIMP‐3 deficiency enhanced tumour growth, angiogenesis, invasion and inflammation (Adissu et al.…”
Section: Discussionmentioning
confidence: 99%
“…GT strategies may also target the catabolic effect of MMPs, by the delivery of TIMPs (Casagrande et al, ; Yang et al, ; Zhang et al, ). Over‐expression of TIMPs in different cell types (including synovial cells) resulted in the inhibition of arthritic joint inflammation in vivo, as well as in the inhibition of tumor growth and vascular endothelial growth factor (VEGF) receptor‐2 in vitro (Chen et al, ; Van der Laan et al, ). Furthermore, to enhance matrix formation applied tactic is the overexpression of growth factors, most importantly the TGF‐β, which was reportedly aiding cartilage regeneration (Guo et al, ; Pagnotto et al, ), and enhanced the healing of meniscal tissues in vitro (Steinert et al, ), showing promise for the future.…”
Section: Advanced Therapiesmentioning
confidence: 99%